Kelayakan Kawasan Nglanggeran, Indonesia sebagai Lokasi Pelepasliaran Burung Pemangsa - Eprilurahman, Rury (Fakultas Biologi Universitas Gadjah Mada, 2025)
The release of birds of prey requires suitable habitats to ensure the success and survival of the species in the wild. This study aimed to conduct a habitat assessment in the Nglanggeran area, Yogyakarta, as a potential release site for birds of prey. The methods included exploratory and stationary observations to record the species, numbers, behavior, and movement of birds of prey, complemented by data collection on other bird species, potential prey, and threats through semi-structured interviews. The results showed that the Nglanggeran area, dominated by teak, mahogany, acacia, and fruit trees, supports birds of prey such as the Crested Serpent Eagle (Spilornis cheela), Spotted Kestrel (Falco moluccensis), Chinese Goshawk (Accipiter soloensis), and Oriental Honey Buzzard (Pernis ptilorhynchus). This habitat was deemed suitable based on the availability of food, nesting sites, and minimal threats. These findings support the potential of Nglanggeran as a release site for birds of prey in the Daerah Istimewa Yogyakarta region.